Student involvement in association and personality development: a study in Universiti Teknologi MARA (UiTM) Seremban 3 / Nazathul Khairunnisa Mazlan and Aimi Annasuha Abd Rahman - Mazlan, Nazathul Khairunnisa; Abd Rahman, Aimi Annasuha (2022)
The goal of this study is to examine the relationship between involvement in university association and personality development which involve leadership skills, communication skills and networking skills. This research used a persuasive sampling involving 385 students in UiTM Kampus Seremban 3. This research intended to establish that there is a relationship between independent variables and dependent variables. This study indicates involvement in university association and personality development. In this study, the survey approached the FSPPP student in UiTM Kampus Seremban 3 by distributing questionnaires successfully insight into the issues. Therefore, the findings of this study demonstrate that every student must participate actively in association in university to ease them to get job opportunities. Moreover, this study shows that by being involved in association, the students get to spread their networking skill and get new knowledge by having networking. This study concludes that involvement in association makes the students acquire personality development by having those skills (leadership skill, communication skills and networking skills).